Value of the strain ratio in the differential diagnosis of intraocular tumors by elastosonography: A retrospective case-control study - Wei Chen; Wenli Yang; Dongjun Li; Ziyang Wang; Qi Zhao; Yifeng Li; Rui Cui; Lin Shen (Indian Journal of Ophthalmology, 2023)
Purpose: To examine the role of the strain ratio in elastosonography for the differential diagnosis of common intraocular tumors such as choroidal melanoma, choroidal hemangioma, choroidal metastatic carcinoma, and retinoblastoma. Methods: This study included patients suffering from intraocular space-occupying lesions and who visited Beijing Tongren Eye Center of Beijing Tongren Hospital affiliated to Capital Medical University from June 2016 to March 2020. All patients underwent a physical examination, fundus examination with mydriasis, color Doppler ultrasonography, elastosonography, magnetic resonance imaging (MRI), and fundus angiography within 1 week. All patients were grouped as choroidal melanoma, choroidal metastatic carcinoma, retinoblastoma, choroidal hemangioma, and optic disk melanocytoma. A receiver operating characteristic (ROC) curve analysis was performed to assess the strain ratio for diagnosing malignant intraocular tumors. Results: A total of 155 patients (161 eyes) were recruited. The strain ratios measured were 39.59 ± 15.92 for choroidal melanoma, 36.85 ± 13.64 for choroidal metastatic carcinoma, 38.93 ± 17.27 for retinoblastoma, 13.42 ± 10.93 for choroidal hemangioma, and 3.84 ± 1.32 for optic disk melanocytoma. The strain ratios of the three malignant lesions were significantly higher than those of the two benign lesions (all P < 0.001). The area under the ROC curve was 0.95 ± 0.028. The optimal cutoff point was 22.67, with 85.7% sensitivity and 96.4% specificity. Conclusion: There were significant differences in elasticity between the malignant and benign intraocular tumors. The strain ratio using elastosonography could serve as an important auxiliary examination to distinguish between benign and malignant intraocular tumors.